L1/Laminin Modulation of Growth Cone Response to EphB Triggers Growth Pauses and Regulates the Microtubule Destabilizing Protein SCG10 - Suh, Leejee H. (J Neurosci, 2004)
During development, EphB proteins serve as axon guidance molecules for retinal ganglion cell axon pathfinding toward the optic nerve head and in midbrain targets. To better understand the mechanisms by which EphB proteins influence retinal growth cone behavior, we investigated how axon responses to EphB were modulated by laminin and L1, two guidance molecules that retinal axons encounter during in vivo pathfinding. Unlike EphB stimulation in the presence of laminin, which triggers typical growth cone collapse, growth cones co-stimulated by L1 did not respond to EphB. Moreover, EphB exposure in the presence of both laminin and L1 resulted in a novel growth cone inhibition manifested as a pause in axon elongation with maintenance of normal growth cone morphology and filopodial activity. Pauses were not associated with loss of growth cone actin but were accompanied by a redistribution of the microtubule cytoskeleton with increased numbers of microtubules extending into filopodia and to the peripheral edge of the growth cone. This phenomenon was accompanied by reduced levels of the growth cone microtubule destabilizing protein SCG10. Antibody blockade of SCG10 function in growth cones resulted in both changes in microtubule distribution and pause responses mirroring those elicited by EphB in the presence of laminin and L1. These results demonstrate that retinal growth cone responsiveness to EphB is regulated by co-impinging signals from other axon guidance molecules. Furthermore, the results are consistent with EphB-mediated axon guidance mechanisms that involve the SCG10-mediated regulation of the growth cone microtubule cytoskeleton.